Peran Determinasi Working Capital Policy terhadap Company Financial Performance - Shaferi, Intan; Laksana, Rio Dhani (Performance, 2019)
Financial decisions in the company are an important part that is very influential on operational and financial performance. The survival of a company is showed from an operational activity that carried out, so that the company gets the desired results. Financial decisions in the form of working capital policies are important for the survival of the company. Companies can use working capital to get good financial performance. Financial performance can be reflected in profitability and firm value. The role of working capital towards financial performance in companies involves other factors, namely firm size. Large companies with assets have quite a lot of different policies on the use of working capital. This impact will affect the financial performance produced. Associated with the size of the company, this study examines working capital for financial performance by considering firm size. The study aims to examine working capital for financial performance. The study was conducted on manufacturing companies in the Indonesia Stock Exchange with a study period of three years 2015 to 2017. Test results showed the relationship of working capital to financial performance by considering firm size. With this connection, it shows the importance of using woking capital that is good enough to generate profitability and firm value.   Keywords: working capital, financial performance, profitability, firm value, firm size.